1993
DOI: 10.1039/dt9930000533
|View full text |Cite
|
Sign up to set email alerts
|

Structural systematics. Part 5. Conformation and bonding in the chiral metal complexes [M(η5-C5R5)(XO)Z(PPh3)]

Abstract: Data were retrieved from the Cambridge Structural Database for 67 crystal structures containing suitable geometric data for 74 molecular fragments of the form [M(q5-C5R5) (XO)Z(PPh,)] 1 (X = C or N; Z = any ligand). These data were analysed to examine the conformational preferences for the triphenylphosphine ligand in respect of orientations about the M-P bond and about the P-C bonds of the attached phenyl groups, and the mechanisms by which the preferred conformers interconvert. There are two main diastereome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…[25] Interconversion of the M/P isomers appears to be rapid at room temperature, as the 1 Ha nd 31 PNMR spectra of 16 obtained by recrystallisation each contain only as ingle set of signals. [26] Following dissolution of af urtherb atch of 11 (d.r. = 20:1) in dichloromethane, addition of tetrabutylammoniumc hloride (TBAC)a gain resulted in an immediate change in colour to orange (see SupportingI nformation), followed by isolation of the crude chloride adduct 12.D ue to broad signals in the 1 HNMR spectrum of this compound,t he diastereomeric purity was not clear.A ddition to 12 of KPF 6 in acetonitrile reformed 11 with ad .r.o f2 0:1, revealing no overall stereochemical leakage.…”
Section: Asymmetrics Ynthesis Of Planar-chiral Iridacyclesmentioning
confidence: 99%
“…[25] Interconversion of the M/P isomers appears to be rapid at room temperature, as the 1 Ha nd 31 PNMR spectra of 16 obtained by recrystallisation each contain only as ingle set of signals. [26] Following dissolution of af urtherb atch of 11 (d.r. = 20:1) in dichloromethane, addition of tetrabutylammoniumc hloride (TBAC)a gain resulted in an immediate change in colour to orange (see SupportingI nformation), followed by isolation of the crude chloride adduct 12.D ue to broad signals in the 1 HNMR spectrum of this compound,t he diastereomeric purity was not clear.A ddition to 12 of KPF 6 in acetonitrile reformed 11 with ad .r.o f2 0:1, revealing no overall stereochemical leakage.…”
Section: Asymmetrics Ynthesis Of Planar-chiral Iridacyclesmentioning
confidence: 99%
“…57,62-64 p-Backbonding into the PR 3 s* MOs should result in longer P-R bonds and a more pyramidal P; weakening of such an orbital interaction should result in the opposite effect, as observed. Consequently, the structural changes in M-P distances and geometric changes within the ligand have been rationalized as resulting from depopulation of the M/PR 3 s* interaction on oxidation coupled with a general decrease in backbonding as the metal orbitals in the oxidized form drop further away from the PR 3 s* MO energies, resulting in a poorer energy match 57,[62][63][64]. Computational evidence for this depopulation was provided by examination of the Fukui function of the reduced partner of the pair; this function allows identification of which electrons are most easily distorted by an electrophile and therefore which orbitals are most vulnerable to depopulation in an oxidation process 65.…”
mentioning
confidence: 99%
“…There is a clear relationship between this symmetrical system and others for two phenyl rotors attached to a phosphorus atom [such as in M(dppe), M("-dppm), MPPh 3 and M(tripod) complexes] (see, for example, Morton & Orpen, 1992;Garner & Orpen, 1993;Hunger et al, 1998) previously studied. In all these cases the CSD studies show that the high-energy region around (0, 0) in the notation of this paper is devoid of structures and the populated regions lie within those regions populated in the [M 2 {"-PPh 2 }] system.…”
Section: Discussionmentioning
confidence: 75%
“…This family includes, of course, all PPh 3 complexes (Bye et al, 1982), as well as the organic archetype diphenylmethane, CH 2 Ph 2 (Dunitz, 1979), and a wide range of EAr 2 and EAr 3 species (E = B, C, N, O or S;see, for example, Mislow, 1976;Rappoport et al, 1990;Klebe, 1994;Rappoport & Biali, 1997). Although some notable studies of more complex systems containing PPh 2 moieties have been reported, including several on triphenylphosphine species (Bye et al, 1982;Norskov-Lauritsen & Bu È rgi, 1985;Garner & Orpen, 1993) and chelating bis(diphenylphosphino)alkanes (Morton & Orpen, 1992;Hunger et al, 1998), there has been no study reported on the conformational behaviour of this, the simplest diphenylphosphorus member of this family of diaryl rotor systems. The approach taken in this work is twofold: ®rstly, we have studied the conformations of [M 2 {"-PPh 2 }] species in crystal structures in the Cambridge Structural Database (CSD; Allen & Kennard, 1993) and, secondly, for comparison, the potential energy of a representative species [(AuBr) 2 {"-PPh 2 }] À has been evaluated using molecular mechanics methods.…”
Section: Introductionmentioning
confidence: 99%